The Effect of Physical Activity on Bone Biomarkers in People With Osteoporosis: A Systematic Review - Marini, Sofia; Barone, Giuseppe; Masini, Alice; Dallolio, Laura; Bragonzoni, Laura; Longobucco, Yari; Maffei, Francesca (Frontiers in Endocrinology, 2020)
Background: Bone imbalance between anabolic and catabolic processes at the level of remodeling unit due to the prevalence of resorbing activity, represents a health problem of ageing. The consequence is the negative balance of bone turnover that can lead to osteoporosis. Physical activity (PA) can play a central role in the comprehensive management of osteoporosis, since it induces the anabolism of bone tissue. Bone turnover biomarkers, reflecting the cellular activity linked to bone metabolism, can represent an evaluation tool to assess the efficacy of PA in the osteoporotic population. The aim of this systematic review, conducted according to the PRISMA statement, was to investigate the effects of PA interventions on bone biomarkers in people with osteoporosis. Methods: A comprehensive literature search of electronic databases was conducted through PubMed, Cochrane, Cinahl, Embase, Trip, to find randomized controlled trials (RCTs) investigating the topic of PA and bone turnover biomarkers in the osteoporosis population. In accordance with the Cochrane risk-of-bias tool, the quality of each study was assessed. Results: Out of 992 identified articles, 136 full texts were screened. Only 3 RTCs matched the eligibility criteria. In one study, sub-maximal aerobic exercise improved Bone-specific alkaline phosphatase (bone formation biomarker) and Amino-terminal Crosslinked Telopeptide of type 1 collagen (bone resorption biomarker) in osteoporotic women. The other two studies showed a positive effect on total alkaline phosphatase (a non-specific bone formation biomarker) in women with osteoporosis. Conclusion: The systematic review revealed possible exercise benefits in terms of improving bone formation and decreasing bone resorption biomarkers in the osteoporotic population. However, these results should be interpreted with caution, especially due to the limited number and poor quality of the studies included. Further research is needed to estimate the influence of PA on bone biomarkers in the osteoporosis management.